DEVELOPMENT OF A STOCK MANAGEMENT SYSTEM USING A LAYERED ARCHITECTURE AND LARAVEL FRAMEWORK: JUSTOCK (CIPEEX, 2025)
This document outlines the development of a stock management system for a variety store, with the primary objective of creating an efficient and user-friendly tool to manage products, inventory, and sales operations. The methodology adopted is based on a layered software architecture, utilizing a web-based front-end and a back-end developed with the Laravel framework in PHP. The front-end handles user interaction, while the back-end manages business logic and data persistence, ensuring a clear separation of concerns and responsibilities. The project integrates software quality principles from the planning phase, with a focus on maintainability, performance, usability, and security. As a result, the system is designed to be scalable, adaptable, and easy to extend, allowing for future modifications and enhancements. The conclusion demonstrates that the chosen architecture and technologies provide a robust foundation for building a high-quality, maintainable, and scalable system with potential for future platform integration.
Keywords: layered architecture; stock management; laravel; software quality